2014
DOI: 10.4174/astr.2014.87.5.239
|View full text |Cite
|
Sign up to set email alerts
|

Increasing utilization of abdominal CT in the Emergency Department of a secondary care center: does it produce better outcomes in caring for pediatric surgical patients?

Abstract: PurposeThe use of abdominal computed tomography (ACT) utilization is increasing to a remarkable extent in the pediatric Emergency Department (ED), but the clinical benefit of increased use of ACT for pediatric surgical patients remains uncertain.MethodsA retrospective review was conducted to investigate if, for patients who had visited pediatric ED during the last 5 years, increasing utilization of ACT would increase the detection rate of acute appendicitis, increase the detection rate of surgical conditions o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…The changes in the incidence rate may be attributed to incidental diagnosis and/or changes in the prevalence of RCC risk factors. Recently, there has been a significant increase in the use of advanced abdominal imaging in the evaluation of unrelated abdominal symptoms (15,16). For example, a recent study found that the frequent use of CT scans is associated with increased risk of undergoing a nephrectomy (17).…”
Section: Discussionmentioning
confidence: 99%
“…The changes in the incidence rate may be attributed to incidental diagnosis and/or changes in the prevalence of RCC risk factors. Recently, there has been a significant increase in the use of advanced abdominal imaging in the evaluation of unrelated abdominal symptoms (15,16). For example, a recent study found that the frequent use of CT scans is associated with increased risk of undergoing a nephrectomy (17).…”
Section: Discussionmentioning
confidence: 99%
“…Recommending ACT as a first-line radiological evaluation is not a key message in our study, and it has already been proven that the increasing utilization of ACT does not decrease the negative appendectomy rate. 20,21 We also believe in the policy of reducing radiation exposure as much as possible, and the purpose of our study was to provide some clues to help differentiate true and negative appendicitis for patients with inconclusive ACT results. As an alternative to ACT, magnetic resonance imaging (MRI) has been shown to have better diagnostic accuracy without the risk of radiation exposure and might supplant the role of ACT in pediatric appendicitis.…”
mentioning
confidence: 99%